MicroRNA Expression Profiling in Age-Dependent Renal Impairment - Yanai, Katsunori; Kaneko, Shohei; Ishii, Hiroki; Aomatsu, Akinori; Hirai, Keiji; Ookawara, Susumu; Morishita, Yoshiyuki (Frontiers in Medicine, 2022)
Background Age-dependent renal impairment contributes to renal dysfunction in both the general population and young and middle-aged patients with renal diseases. Pathological changes in age-dependent renal impairment include glomerulosclerosis and tubulointerstitial fibrosis. The molecules involved in age-dependent renal impairment are not fully elucidated. MicroRNA (miRNA) species were reported to modulate various renal diseases, but the miRNA species involved in age-dependent renal impairment are unclear. Here, we investigated miRNAs in age-dependent renal impairment, and we evaluated their potential as biomarkers and therapeutic targets. Methods We conducted an initial microarray profiling analysis to screen miRNAs whose expression levels changed in kidneys of senescence-accelerated resistant (SAMR1)-10-week-old (wk) mice and SAMR1-50wk mice and senescence-accelerated prone (SAMP1)-10wk mice and SAMP1-50wk mice. We then evaluated the expressions of differentially expressed miRNAs in serum from 13 older patients (>65 years old) with age-dependent renal impairment (estimated glomerular filtration ratio <60 mL/min/1.73 m2) by a quantitative real-time polymerase chain reaction (qRT-PCR) and compared the expressions with those of age-matched subjects with normal renal function. We also administered miRNA mimics or inhibitors (5 nmol) with a non-viral vector (polyethylenimine nanoparticles: PEI-NPs) to SAMP1-20wk mice to investigate the therapeutic effects. Results The qRT-PCR revealed a specific miRNA (miRNA-503-5p) whose level was significantly changed in SAMP1-50wk mouse kidneys in comparison to the controls. The expression level of miRNA-503-5p was upregulated in the serum of the 13 patients with age-dependent renal impairment compared to the age-matched subjects with normal renal function. The administration of a miRNA-503-5p-inhibitor with PEI-NPs decreased the miRNA-503-5p expression levels, resulting in the inhibition of renal fibrosis in mice via an inhibition of a pro-fibrotic signaling pathway and a suppression of glomerulosclerosis in mice by inhibiting intrinsic signaling pathways. Conclusion The serum levels of miRNA-503-5p were decreased in patients with age-dependent renal impairment. However, inhibition of miRNA-503-5p had no effect on age-dependent renal impairment, although inhibition of miRNA-503-5p had therapeutic effects on renal fibrosis and glomerulosclerosis in an in vivo animal model. These results indicate that miRNA-503-5p might be related to age-dependent renal impairment.